Collective Bargaining and Academic Freedom : Are they Compatible? - Woods, H. D. (Relations industrielles / Industrial Relations, 1975)
In this paper, the author supports the idea that collective bargaining presents some real dangers to academic freedom on the campuses of Canadian Universities.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z